Airborne Fungi in Chronic Rhinosinusitis Patients Maxillary Sinus Lavage at Dr. Saiful Anwar Hospital Malang - Maharani, Iriana; Suheryanto, Rus; Retnoningsih, Endang (BALI MEDICAL JOURNAL, 2016)
Background: Chronic rhinosinusitis has a significant impact on the quality of life and health of adult population. Role of airborne fungi remains a controversy and have become the source of discussion for decades. Objective to know the prevalence of airborne fungi in the chronic rhinosinusitis with or without polyps patients and to know the possible effect of airborne fungi on chronic rhinosinusitis inflammation. Methods: This is a cross sectional research in the Saiful Anwar Public Hospital Malang, there were 29 patients involved. We examine fungi culture, H&E staining and DNA fungi by using PCR from sinus lavage sample. From the blood serum we examine allergen specific IgE, IgG3, IL-13 and IL-5. Results: Fungi culture there were 31,03 % of sample growth but only matches the PCR result in 3 samples (10,34 %). From PCR examinations we found all sample were positive with 2-5 species fungi, Alternaria alternata was found positive in 24,13% samples. There was an increment of IgE allergen specific and IL-5, a decrement of IL-13 and IgG3 in all of our samples regardless presence of nasal polyps and species of fungi found in PCR. Conclusions: PCR is a more reliable method compare to fungal culture. The presence of fungi in all of our samples could indicate fungi contribution to the disease pathophysiology. The increased level of Il-5 was not followed by IL-13; it may happen through PRR pathway.